2020
DOI: 10.1021/acs.jctc.9b01104
|View full text |Cite
|
Sign up to set email alerts
|

Could Microwave Irradiation Cause Misfolding of Peptides?

Abstract: Microwaves have been experimentally shown to affect the folding dynamics of peptides and proteins. Using molecular dynamics, we performed all-atom simulations of a model β-peptide in aqueous solution where individual degrees of freedom of solvent molecules were decoupled to allow for investigation at non-equilibrium microwave-irradiated conditions. An elevated rotational temperature of the water medium was found to significantly affect the conformation of the peptide due to the weakened hydrogen-bonding intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Initially, the advent of mobile telephones, radar, satellites, wireless networks, microwave ovens and GPS devices facilitated our lives, but electromagnetic waves are a double-edged sword and we have to think about the negative effects they have on our organism ( 34 ). Cardiac enzymes are specific enzymes which are found which include AST, CK-MB LDH, cTNT.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the advent of mobile telephones, radar, satellites, wireless networks, microwave ovens and GPS devices facilitated our lives, but electromagnetic waves are a double-edged sword and we have to think about the negative effects they have on our organism ( 34 ). Cardiac enzymes are specific enzymes which are found which include AST, CK-MB LDH, cTNT.…”
Section: Discussionmentioning
confidence: 99%
“…144,145 The thermal effects of EF irradiation have been well studied and are easier for interpretation mostly due to the expected inherent denaturation of proteins at increased temperatures. 146–148 The mechanisms of non-thermal EF effects, however, remain poorly understood. This is mostly due to the interconnection of specific EF frequencies and strengths capable of exciting certain vibrational modes of proteins and peptides, causing (sometimes irreversible) structural changes which can affect their structure, behaviour and function.…”
Section: Recent Case Studiesmentioning
confidence: 99%
“…Recently, the ordered polar molecular interaction increases the hydrogen bond of OH groups as the nonthermal microwave effect, which explains the lower chemical shift calibrated-temperature of OH protons . In addition, microwaves can change the spatial conformation between peptides and solvent molecules by weakening the hydrogen bond interactions . The essence of the above results is the interactions between polar molecules and microwave fields. , Our previous work has reported that microwave polarization can change the spatial collision probability of water molecules in the direction of the electric field and the energy distributions, where the fraction of intermediate energy molecules increases while the fraction of high-energy molecules decreases .…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have provided substantial evidence for the existence of the microwave nonthermal effect. As for a theoretical research, the physical mechanism of the microwave nonthermal effect is also being further understood and improved. Early, a reliable viewpoint about the microwave nonthermal effect is that microwave can speed up the overall reaction rate by promoting the diffusion of reactant molecules . Then, the effective intramolecular potential energy surface under the action of microwave field shows that the nonthermal effect caused by potential distortion exists in the intramolecular reaction .…”
Section: Introductionmentioning
confidence: 99%